Memory Crash : Politics of History in and around Ukraine, 1980s–2010s - Kasʹi︠a︡nov, H. V. (Heorhiĭ Volodymyrovych), 1961- (Book collections on Project MUSE., 2021)
"This account of historical politics in Ukraine, framed in a broader European context, shows how social, political, and cultural groups have used and misused the past from the final years of the Soviet Union to 2020"--